The Brazilian experience on screening, visual assessment, and prescription of glasses in childhood: A perspective of global interest - ACSB Carneiro; JM Furtado; AL Silva; ALF Darcie; AC Ribeiro; LM Hopker; C Nakanami; SP Donahue; JD Rossetto (AJO International)
Purpose: This perspective presents evidence-based guidelines developed by a representative expert group from Brazil. The guidelines aim to enhance pediatric eye care through structured screening protocols, comprehensive eye examinations, and effective eyeglass prescriptions tailored to local contexts. Methods: The guidelines were developed through a narrative literature review and expert consensus among Brazilian Society of Pediatric Ophthalmology members, utilizing a comprehensive search strategy on PubMed from September 2022 to July 2024. Results: Key recommendations include performing the red reflex test (RRT) before neonatal discharge and repeating it at least three times per year during the first three years of life. Additional recommendations include initiating photoscreening at one year of age and conducting visual acuity screening between ages 3 and 5—prioritizing age 5 for amblyopia detection—and again at ages 10–11. Follow-up screenings are advised at critical developmental stages. To expand access, trained non-ophthalmology professionals should participate in screening efforts within existing healthcare frameworks. Scaling secondary and tertiary care and aligning the program with other governmental initiatives are essential for sustainability and impact. Additionally, structuring the health program to align with other government initiatives will help ensure its sustainability and long-term impact. Conclusion: These guidelines provide a solid foundation for effective pediatric eye health programs, contributing to broader public health and sustainable development goals.